Kajian Serat dan Komponen Aktif Beras Analog dari Rumput Laut Gracilaria sp.: Study of Fibre and Active Components of Rice Analogue from Seaweed Gracilaria sp. - Sri Purwaningsih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Indonesia is the highest exporter of Gracilaria sp. seaweed and this seaweed contains high dietary fiber (64.74%), and also strong antioxidant activity. The aim of the study was to determine the best formula based on fiber levels, phenols, tannins, and flavonoids from rice analogue from Gracilaria sp. Determination of rice analogue from seaweed Gracilaria sp. used complete random design (RAL), with three repeats, if the test results showed real difference than continued with duncan's test at a confidence level of 95%. The concentration of treatment is the addition of 0, 10, 13, and 16%. The resultsed of analysis according to the Codex Alimentarius Commission (2009) included foods of high fiber sources, with range of 6.09-10.77%. It contains bioactive components (alkaloids, phenols, tannins, and flavonoids). The content of phenols, tannins, flavonoids ranges from 160,32-192,89 mg/ kg; 0,14-0,24%; 4,02-5,18 mg QE/g. The best formulation of rice analogue from based on fiber, phenols, tannins, flavonoids levels was at a concentration of 13%